6‐1: Invited Paper: Measuring Health Parameters with Large‐Area Organic Photodetector Arrays. Issue 1 (28th June 2021) - Akkerman, Hylke; Peeters, Bart; van Breemen, Albert; Shanmugam, Santhosh; Lopez, Leslye Ugalde; Tordera, Daniel; Delvitto, Ezequiel; Simone, Giulio; van de Ketterij, Richard; Kronemeijer, Auke Jisk; Meulenkamp, Eric; Gelinck, Gerwin
Abstract : Solution‐processed organic photodetectors (OPDs) have witnessed great progress in the past few years. With silicon‐like performance achieved, OPDs enable new medical imaging applications by offering cost‐effective light detection over large area. Herein, we illustrate the compelling advantages of high spatial and temporal resolution OPD arrays for medical X‐ray detectors and wearable pulse oximeters.